Bargaining for bribes under uncertainty - Serra, D (2008)
A corrupt transaction is often the result of bargaining between the parties involved. This paper models bribery as a double auction where a private citizen and a public official strategically interact as the potential buyer and the potential seller of a corrupt service. Individuals differ in the internalized moral cost generated by corruption, and may have only imperfect information on others' moral cost, i.e. their "corruptibility". This paper investigates the role the imperfect information with respect to the "corruptibility" of one's potential partner in corruption plays in his or her propensity to engage in bribery, and, consequently, the equilibrium level of corruption in a society. We find that corruption is lower when potential bribers and potential bribees are uncertain regarding each other's "corruptibility". This paper provides therefore theoretical support to anti-corruption strategies, such as staff rotation in public offices, aimed at decreasing the social closeness of bribers and bribees.